AMPK in cardiac fibrosis and repair: Actions beyond metabolic regulation. (February 2016) - Daskalopoulos, Evangelos P.; Dufeys, Cécile; Bertrand, Luc; Beauloye, Christophe; Horman, Sandrine
Abstract: Fibrosis is a general term encompassing a plethora of pathologies that span all systems and is marked by increased deposition of collagen. Injury of variable etiology gives rise to complex cascades involving several cell-types and molecular signals, leading to the excessive accumulation of extracellular matrix that promotes fibrosis and eventually leads to organ failure. Cardiac fibrosis is a dynamic process associated notably with ischemia, hypertrophy, volume- and pressure-overload, aging and diabetes mellitus. It has profoundly deleterious consequences on the normal architecture and functioning of the myocardium and is associated with considerable mortality and morbidity. The AMP-activated protein kinase (AMPK) is a ubiquitously expressed cellular energy sensor and an essential component of the adaptive response to cardiomyocyte stress that occurs during ischemia. Nevertheless, its actions extend well beyond its energy-regulating role and it appears to possess an essential role in regulating fibrosis of the myocardium. In this review paper, we will summarize the main elements and crucial players of cardiac fibrosis. In addition, we will provide an overview of the diverse roles of AMPK in the heart and discuss in detail its implication in cardiac fibrosis. Lastly, we will highlight the recently published literature concerning AMPK-targeting current therapy and novel strategies aiming to attenuate fibrosis. Highlights: AMPK limits fibrosis and adverse LV remodeling by acting on cardiomyocytes and CFs. AMPK increases the survival of cardiomyocytes during ischemia. AMPK contributes to the formation of a mature collagen scar after MI. AMPK counteracts pro-fibrotic signals responsible for cardiac interstitial fibrosis. Drugs activating AMPK confer favorable anti-fibrotic effects in the heart.